A fal, amit kerítésnek hívunk - Hajdú, András D., 1981-; Szabó, Balázs; Magócsi, Márton (Hungary, 2012)
Poverty and uncertainty are the plight of the Roma living in the slums outside the Transylvanian town of Baia Mare (Nagybánya), Romania. The mayor wants to destroy the shacks they live in and remove them from a block of flats, which is barricaded by a wall from the rest of the neighborhood. According to the local council, the separating wall is merely a protective fence, and the plan to move the Roma outside the city is a safety measure.
Verzio Film Festival Submission
Keywords: Hungary